Clinical Efficacy of a Spiral CT-Guided Balloon Compression Day-Surgery Operation for the Treatment of Trigeminal Neuralgia - Xu, Bing; Jia, Zi-pu; Ren, Hao; Meng, Lan; Shen, Ying; Wang, Tao; Luo, Fang; Lv, Rui (Frontiers in Neurology, 2022)
Objective: This study aimed to investigate the clinical efficacy of a balloon compression day-surgery operation under the guidance of spiral computed tomography (CT) three-dimensional reconstruction for the treatment of trigeminal neuralgia. Methods: The clinical efficacy and related indexes of 380 patients with trigeminal neuralgia treated by a spiral CT-guided balloon compression day-surgery operation in the pain department of Beijing TianTan Hospital, from October 2017 to March 2021, were retrospectively analyzed. Results: Five patients failed due to foramen ovale puncture or in placing the balloon; two patients had ineffective results after the operation and re-entered the hospital for secondary balloon compression. The initial effective rate of the operation in the 380 patients was 98.16%. All patients were discharged on the day of the operation, the average operation time was 26.46 ± 12.15 minutes, and the average interval from the completion of the operation to discharge was 2.67 ± 0.95 hours. During the follow-up period (1–41 months), 12 patients had pain recurrence, and a Kaplan–Meier analysis revealed that the cumulative pain-free recurrence survival rate at 41 months after the operation was 80.64%. No complications related to foramen ovale puncture occurred. Conclusion: The spiral CT-guided balloon compression day-surgery operation is safe, effective, and worthy of clinical promotion.